Identifying trade-offs and reference points in support of ecosystem approaches to managing Gulf of Mexico menhaden - Berenshtein, Igal; Sagarese, Skyler R.; Lauretta, Matthew V.; Schueller, Amy M.; Chagaris, David D. (Frontiers in Marine Science, 2023)
Gulf menhaden (Brevoortia patronus) support the largest fishery by yield in the Gulf of Mexico (GoM) and are a key forage species for many marine predators. While menhaden stock assessments indicated that overfishing was not likely to have occurred in the past, concerns have been raised regarding the possible effects of menhaden fishing on their predators. In this study, we used a US Gulfwide Ecopath with Ecosim (EwE) model to explore the predicted effects of increased menhaden harvest on the GoM ecosystem and focused our analyses on Gulf menhaden predators. Key menhaden predators identified included king mackerel (Scomberomorus cavalla), Spanish mackerel (Scomberomorus maculatus), sea trout (Cynoscion spp.), red drum (Sciaenops ocellatus), and pelagic coastal piscivores [e.g., bluefish (Pomatomus saltatrix)]. As expected, these predators exhibited reduced biomass in response to increased Gulf menhaden harvest, with a predicted 11% decrease in predator biomass at simulated fishing levels near historical highs. Our results indicate strong relationships between the effects of menhaden fishing and the predator fishing mortality for king mackerel and intermediate relationships for Spanish mackerel, blacktip shark (Carcharhinus limbatus), red drum, large coastal sharks, and pelagic coastal piscivores. Biomass of predator groups such as demersal coastal invertebrate feeders [e.g., drums and croakers (Sciaenidae)] are more affected by menhaden harvest (through trophodynamics interactions and bycatch removal) compared to the isolated effect of their fishing mortality. For almost all the groups examined in the trade-off analysis, with the exception of sea trout, current biomass (2016) was higher than their target biomass representing 75% of their biomass at maximum sustainable yield. In comparison to the time series of fishing mortality rates estimated by the most recent Gulf menhaden stock assessment, the mean ecological reference point (ERP) of 0.862 was exceeded in all but 1 year from 1977 to 2007; however, neither the target nor threshold upper ERP value has been exceeded since 2008. The observed Gulf menhaden landings from 2003 to the present were generally within the range of the projected equilibrium landings (i.e., within confidence intervals) at both the ERP target and threshold values except for three recent years.